PENYELESAIAN PEMBIAYAAN YANG MACET PADA MASA PANDEMI COVID-19 DI PT. BFI FINANCE CABANG MATARAM - I GEDE PUTU PURNAMIA; Zaenal Arifin Dilaga (Private Law, 2023)
The purpose of this research is to determine solutions for delinquent financing during the Covid-19 pandemic at PT. BFI Finance Mataram Branch and to identify the challenges in resolving delinquent financing during the Covid-19 pandemic at PT. BFI Finance Mataram. This research is a normative-empirical study, employing the statutory approach, conceptual approach, and sociological approach as the methods of analysis. The data sources include field data and literature data, consisting of primary and secondary data. The data collection techniques involve conducting interviews for field data and document study for literature data. The data analysis is conducted through descriptive qualitative analysis. The research findings conclude that in resolving delinquent loans during the Covid-19 pandemic, PT. BFI Finance provides relief measures, such as rescheduling payment schedules, to alleviate the burden on customers. The non-litigation negotiation method is being used due to the pandemic situation. However, the challenges faced in resolving delinquent financing during the pandemic are mainly attributed to the financial problems faced by the debtors. Many debtors have been laid off by their employers during the pandemic, and it has been difficult for BFI to reach out to them due to the pandemic situation.